Organizational citizenship behaviour as a protective factor against the occurrence of adverse nursing‐sensitive outcomes: A multilevel investigation. (14th October 2022) - Mazzetti, Greta; Sciolino, Lorenzo; Guglielmi, Dina; Mongardi, Maria; Nielsen, Karina; Dawson, Jeremy
Abstract: Aims: This study aimed to investigate the association between organizational citizenship behaviour enacted by nurses and the occurrence of adverse nursing‐sensitive patient outcomes. Background: Managing psychosocial factors (i.e., aspects concerning the work environment) is key to ensure patient safety, to prevent exacerbation of case complexity and to cope with critical shortages in human and financial resources. Methods: Self‐report measures of nurses' organizational citizenship behaviour were combined with objective data on the incidence of adverse nursing‐sensitive outcomes (i.e., pressure ulcers and restraint use) collected through patients' medical records. Participants were 11, 345 patients and 1346 nurses across 52 teams working in 14 Italian hospitals. Data were analysed using multilevel binary logistic regression models. Results: A negative relationship between nurses' organizational citizenship behaviour and restraint use was identified, with an odds ratio of 0.11. Thus, for a one‐unit higher organizational citizenship behaviour score, the odds of using restraints shrink to about one eighth of the previous level. Conclusions: Intervention strategies to foster the implementation of organizational citizenship behaviour among nurses may inhibit the occurrence of critical outcomes affecting patients' health and well‐being (i.e., using restraint devices). Implications for Nursing Management: In health care organizations, shaping a psychosocial environment encouraging organizational citizenship behaviour can mitigate the occurrence of adverse nursing‐sensitive outcomes such as restraint use on patients.